Living with oversized spring‐loaded vapor relief valves. Issue 1 (18th August 2021) - Smith, Dustin; Paul, Ken
Abstract: Pressure relief valves are installed on pressurized systems to mitigate consequences related to excessive pressure. Since relief valves come in discrete sizes, a relief system designer specifies a relief device with a rated capacity greater than the largest required relief rate. An oversized relief device is one in which a credible overpressure scenario exists; that is, the relief device capacity is more than a multiple (typically five times) the scenario's required relief rate. Most systems have more than one credible overpressure scenario (e.g., external fire or blocked outlet). In some other cases, installations in vapor service have been identified with an oversized relief device concern, without verification of whether or not these installations have a history of instability‐related damage (e.g., excessive relief device damage). Typically damage from oversized vapor relief devices is less severe than chatter which is caused by the coupling of the inlet line and the relief device, not the flow through the relief device. Some owners/operators have specified that oversized relief devices require mitigation. However, this paper shows why an oversized relief device in vapor service may not require mitigation.